Proportionality balancing and constitutional governance : a comparative and global approach - Stone Sweet, Alec; Mathews, Jud (Oxford, United Kingdom : Oxford University Press, 2019)
The book examines the law and politics of rights protection in democracies, and in human rights regimes in Europe, the Americas, and Africa.
1: Constitutions, Rights, and Judicial Power2: Proportionality and Constitutional Governance3: Emergence and Diffusion4: All Things in Proportion? The United States5: Constitutional Dialogues6: Global Constitutionalism and Transnational GovernanceTable of cases
Includes bibliographical references (pages 207-222) and index.
Keywords: Human rights -- Government policy; Public interest; Judicial review; Constitutional law